Application of ultrasound-guided coaxial needle biopsy combined with gelatin sponge plugging in pediatric liver biopsy - Zeng, Keyu; Yu, Boyang; Wu, Zhe; Zhou, Jiehong; Lu, Qiang (Frontiers in Pediatrics, 2025)
PurposeThe aim of this study was to assess the performance of utilizing the coaxial technique in conjunction with gelatin sponge slurry plugging for ultrasound-guided liver biopsy in children.MethodsWe conducted a retrospective study of children undergoing ultrasound-guided coaxial liver biopsy at our institution between March 2020 and March 2025. Participants were stratified into two intervention groups: those receiving gelatin sponge tract embolization vs. batroxobin administered through needle tract. Through comprehensive electronic medical record review, we systematically extracted and compared the following outcome measures: (a) overall complication rates, (b) hemorrhage rates.ResultsThis study included 48 children, with 30 allocated to the gelatin sponge group and 18 to the batroxobin group. The gelatin sponge group demonstrated 9 complications (30.0%, 9/30), consisting of 5 pain events and 4 febrile episodes, while the batroxobin group experienced 6 complications (33.3%, 6/18), including 2 hemorrhage cases, 3 pain events, and 1 febrile episode. The overall complication rates showed no statistically significant difference between groups (30.0% vs. 33.3%, P = 0.809). However, a significant divergence was observed in hemorrhage incidence, with the gelatin sponge group demonstrating superior safety (0% vs. 11.1%, P = 0.044).ConclusionCompared to batroxobin tract injection, coaxial technique in conjunction with gelatin sponge slurry plugging significantly reduced hemorrhagic complications in liver biopsies for children, demonstrating superior safety. The finding supported its adoption as the preferred hemostatic method in children undergoing percutaneous liver biopsy.